Survivor Memorials : Remembering Trauma and Loss in Contemporary Australia - Atkinson-Phillips, Alison (University of New South Wales Press : UWA Publishing, 2019)
This is a book about memorials -- specifically about a new type of memorial that commemorates experiences of survivors. These new memorials acknowledge loss and trauma that people have lived through, rather than died because of. It is also a book about why people feel the need to remember such difficult experiences. As such, it combines a topic that has strong scholarly interest with human stories of pain and resilience from Australia's recent history. The first half of the book outlines the emergence of this new genre of commemoration in three stages: early explorations through community and p.